Effect of ectomycorrhizae on growth and establishment of sal (Shorea robusta) seedlings in central India - ABHISHEK PYASI; KRISHNA KANT SONI; RAM KEERTI VERMA (Nusantara Bioscience, 2013)
Abstract. Pyasi A, Soni KK, Verma RK. 2013. Effect of ectomycorrhizae on growth and establishment of sal (Shorea robusta) seedlings in central India. Nusantara Bioscience 5: 44-49. The aim of the present study was to develop ectomycorrhiza in sal sapling outside the sal growing areas. For this purpose sal seedling were raised at Jabalpur which is around 80 km away from natural sal forest (Motinala, Madhya Pradesh, India). Seed sowing was done with inoculation of ectomycorrhizal inocula prepared by isolating the fungi from surface sterilized young basidiocarp of Lycoperdon compactum and Russula michiganensis. The inocula of ectomycorrhizal fungus were prepared in wheat grains treated with gypsum. The synthesis of ectomycorrhiza was observed in the sapling planted in the experimental field at Jabalpur with production of basidiocarp of Lycoperdon compactum near saplings. The mycorrhized saplings also showed higher growth indices.